2019
DOI: 10.3390/nu11071658
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Weekday and Weekend Sleep with Children’s Reported Eating in the Absence of Hunger

Abstract: Insufficient average sleep duration has been inconsistently associated with poor diet and obesity risks in youth. Inconsistencies in findings across studies may be due to a general failure to examine associations in weekday versus weekend sleep. We hypothesized that greater variations in weekday and weekend sleep duration would be associated with more disinhibited eating behaviors, which, in turn, might be involved in the relationship between sleep and weight. We, therefore, examined, among healthy, non-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…insulin, ghrelin and leptin) that may in turn alter eating behaviors and increase food intake 43 45 . Indeed, weekend “catch-up” sleep has been associated with eating in the absence of hunger, or eating past satiation in response to fatigue, negative affect, or when cued by external circumstances such as the sight or smell of food 46 . However, none of these studies examined sex-specific relationship between sleep variability and obesity, and it is unclear what factors account for the stronger relationship among females in our study, a finding that needs to be confirmed by future studies.…”
Section: Discussionmentioning
confidence: 99%
“…insulin, ghrelin and leptin) that may in turn alter eating behaviors and increase food intake 43 45 . Indeed, weekend “catch-up” sleep has been associated with eating in the absence of hunger, or eating past satiation in response to fatigue, negative affect, or when cued by external circumstances such as the sight or smell of food 46 . However, none of these studies examined sex-specific relationship between sleep variability and obesity, and it is unclear what factors account for the stronger relationship among females in our study, a finding that needs to be confirmed by future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In older age groups, whose nightly sleep is typically less variable, any fluctuations may be more likely to be pathological or deleterious to metabolic health. Notably, some research has found differences between weekend and weekday sleep to be associated with increased hunger, but not with increased fat mass [ 27 ]. However, conflicts in the literature are apparent with another study finding that such difference was associated with an array of metabolic risk factors, including adiposity, in adults aged 30–54 years [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, according to a recent review, the evidence between fluctuations in sleep duration between weekday and weekend nights and metabolic risk in young people is limited and inconclusive [ 26 ]. There is, however, a growing body of literature indicating that the difference between weekend and weekday night sleep is associated with unhealthy changes to eating behaviours and diet quality, though this is heavily reliant on cross-sectional data [ 27 , 28 ]. Eating behaviours and diet quality would likely lie on a causative pathway between sleep and metabolic risk.…”
Section: Introductionmentioning
confidence: 99%
“…Study 1 is an ongoing observational longitudinal study initiated in 2015 (http://clinicaltrials.gov ID# NCT02390765); other findings have been previously reported 26‐28 . Participants were non‐treatment‐seeking boys and girls, 8 to 17 years old.…”
Section: Methodsmentioning
confidence: 99%